The effect of instability resistance training on balance ability among athletes: a systematic review - Jianxin Gao; Xinxin Fu; Hang Xu; Qi Guo; Xiaopeng Wang (Frontiers in Physiology)
BackgroundInstability resistance training (IRT) has been the focus of extensive research because of its proven benefits to balance ability, core stability, and sports performance for athletes. However, there is a lack of systematic reviews explicitly evaluating IRT’s impact on athletes’ balance ability. This study aims to conduct a systematic review of the effects of IRT on balance ability among athletes.MethodThis study used guidelines for the systematic review and meta-analysis of PRISMA, Web of Science, EBSCOhost (SPORTDiscus), PubMed, Scopus, and Google Scholar to collect original references in electronic databases. The PICOS method was selected for the inclusion criteria. The physiotherapy evidence database (PEDro) scale was used to assess the scoring for articles’ risk range of bias. The scoring of 20 studies ranges from 4–8, and study quality is moderate to high.ResultsOut of 285 identified studies, only 20 articles fulfilled all the eligibility criteria after screening. IRT could significantly improve reciprocal, static, and dynamic balance ability among judo athletes, basketball players, weightlifters, archery athletes, soccer players, rhythmic gymnasts, badminton players, track and field athletes, handball players, volleyball players, and gymnasts using unstable surfaces or environments (i.e., BOSU, Swiss, Wobble boards, Suspension trainer, Sissel pillows, Inflated disc and foam surface, Airex balance pad, Togu power ball, Thera-Band, Elastic band strap, Sand surface and so on).ConclusionThe finding suggests that different types of IRT benefit athletes as this training method can effectively enhance reciprocal, static, and dynamic balance ability in athletes. Therefore, this review suggests that IRT should be considered in athletes’ daily training routines for the physical fitness of reciprocal, static, and dynamic balance ability.